2019
DOI: 10.3390/cells8040355
|View full text |Cite
|
Sign up to set email alerts
|

NFκB- and MAP-Kinase Signaling Contribute to the Activation of Murine Myeloid Dendritic Cells by a Flagellin A: Allergen Fusion Protein

Abstract: Fusion proteins incorporating the TLR5-ligand flagellin are currently undergoing clinical trials as vaccine candidates for many diseases. We recently reported a flagellin:allergen fusion protein containing the TLR5-ligand flagellin A (FlaA) from Listeria monocytogenes and the major birch pollen allergen Bet v 1 (rFlaA:Betv1) to prevent allergic sensitization in an experimental mouse model. This study analyzes the signaling pathways contributing to rFlaA:Betv1-mediated pro- and anti-inflammatory cytokine secret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 69 publications
3
15
0
Order By: Relevance
“…The MAP kinase activation leads to protein phosphorylation processes, which result in leukotriene and prostaglandin arising. The MAP kinase modifies the transcription factors as well ( Steelman et al, 2015 ; Draber et al, 2016 ; Moeller et al, 2019 ).…”
Section: Sensitization Hypersensitivity/allergic Reactionsmentioning
confidence: 99%
“…The MAP kinase activation leads to protein phosphorylation processes, which result in leukotriene and prostaglandin arising. The MAP kinase modifies the transcription factors as well ( Steelman et al, 2015 ; Draber et al, 2016 ; Moeller et al, 2019 ).…”
Section: Sensitization Hypersensitivity/allergic Reactionsmentioning
confidence: 99%
“…The decreased expression of multiple surface markers and secretion of several cytokines suggests that Tmod1 deficiency may affect the activities of upstream signaling pathways. TLR4 is the receptor for LPS and its downstream MyD88-dependent pathway activates NF-κB and MAPK pathways, which in turn are responsible for the expression of costimulatory molecules and inflammatory cytokines ( 44 , 45 ). Therefore, we compared the activities of these two pathways in LPS-treated Tmod1 +/+ and TOT/Tmod1 -/- imDCs using western blotting.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous studies showed that MAPK-mediated activation of both NFκB- and mTOR-signaling likely is a key pathway for IL-10 secretion in TLR5-engaged BMDCs with a flagellin:allergen fusion protein [ 20 , 21 ]. However, in the present study, mechanistically, Man2 activated MAPKs (p38, p42/44, SAP/JNK) and NF-κB at certain levels, but only marginally activated p70S6K in BMDCs.…”
Section: Discussionmentioning
confidence: 99%
“…However, in contrast to IL-10 secretion, secretions of IL-6 and TNF-α were detectable after 72 h culture of Man2-treated BMDCs, similar to the observations in LPS-stimulated cells. Several studies have reported TLR-ligands to induce IL-6 and TNF-α production by activating MAPKs and NF-κB in BMDCs [ 16 , 21 , 23 ]. In addition, recent studies described that a shift from oxidative phosphorylation to anaerobic glycolysis in the metabolism of macrophages and DCs is important for pro-inflammatory cytokine production and effector function of the respective cells [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%